Pengaruh Penerapan Strategi Pembelajaran Aktif Tipe Leaming Start With A Question Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII SMPN 2 Padang - SYUKRA RIZAL AHADI (Jurnal Edukasi dan Penelitian Matematika, 2019)
The ability to solve mathematical problems is one of the leaming objectives that is expected to be achieved by students during the mathematics leaming process. But in reality the ability to solve mathematical problems of grade VIII students of SMPN 2 Padang is still low. One effort to solve these problems is to apply an leaming start with a question type active leaming strategy. This type of research is a pre-experiment (pre-experimental) research design with one group pre-test post-test design. The results of this research indicate that an increase in mathematical problem solving abilities of students who leam to use LSQ type active leaming strategies. This is evident from the results of the hypothes test obtained P-Value = 0,000 <α = 0.05 Keyword – Mathematical problem solving ability, Leaming Start with a Question